BENARD CELLS – A POSSIBLE MECHANISM OF THE FORMATION OF SUBAQUATIC AND SUBFLUIDIC STALACTITES - V.A. Popov; M.V. Tsyganko (Минералогия)
The mechanism of formation of stalactites in gravity field of the Earth during their formation in air and subaquatic and subfluidic (magmatic) systems is considered. If the systems represent the cavities in solid bodies with ambient capillary-porous space filled with liquids, then it locally yields the convective subsystems: the Benard cells fixed by the formation of stalactites. The phenomenon is illustrated on examples of malachite, goethite, chalcedony, quartz-feldspar and magnetite stalactites.